Efficacy of Low-Level Laser Therapy for the Treatment of Reproductive System Disorders: A Study of Sensitivity and Outcomes - Meerim Osmonova, Arystanbek Atykanov, Meerim Moldokanova, Kamilla Kerimkulova, Meerim Makambaeva, Altynai Zhumabekova, (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Low-level laser therapy (LLLT) is a noninvasive treatment that stimulates cellular activity through photochemical processes. This study evaluated the efficacy of LLLT in the treatment of various reproductive system disorders, including tubo-ovarian abscesses (TOA), ovarian endometriomas, fallopian tubal patency, and tubo-peritoneal factor infertility. Materials and Methods: A total of 213 women of reproductive age were included in this study. Sensitivity (Se) to LLLT was assessed using refractometry and polarization photometry. Oxidative stress (OS) markers, such as lipid hydroperoxides (LHP), diene conjugates (DCs), overall antioxidant activity (AOA), and catalase activity (CAT), were measured. Results: The optical density and area of the optically active structures significantly increased after LLLT in all groups. Significant differences in OS markers were found among groups before LLLT. After LLLT, women with TOA showed a decrease in DC levels and an increase in CAT, whereas those with ovarian endometriomas exhibited a decrease in LHPs and DC levels, and an increase in AOA and CAT. Women with fallopian tubal patency had decreased DC levels and increased AOA. The Se and specificity (Sp) of ovarian reserve indicators for uterine appendage pathology were highest for DCs (Se = 84–95%, Sp = 80–92%). Conclusion: These findings suggest that LLLT is an effective treatment for various reproductive system disorders, and that individual Se to LLLT should be considered to enhance treatment efficacy.